2022
DOI: 10.1186/s12870-021-03370-2
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal symbiosis promotes the nutrient content accumulation and affects the root exudates in maize

Abstract: Background Arbuscular mycorrhizal fungi (AMF) are a group of important symbiotic microorganisms found in ecosystems. Maize is the second most produced food crop globally. To investigate the mechanisms by which mycorrhizal symbiosis improves maize yields, the effects of mycorrhizal symbiosis on root vigor, nutrient accumulation in various tissues, and root exudates were investigated. We propose the following hypothesis: The secretion of organic acids in root exudates has antagonistic or synergis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…Isolation, concentration, and determination of maize root exudates were performed by reference to Ma ( Ma et al., 2022 ). Briefly, the maize was carefully removed from the pots, cleaned of impurities on the surface of the net root system, and then transferred to a 2 L beaker after rinsing three times with sterile water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolation, concentration, and determination of maize root exudates were performed by reference to Ma ( Ma et al., 2022 ). Briefly, the maize was carefully removed from the pots, cleaned of impurities on the surface of the net root system, and then transferred to a 2 L beaker after rinsing three times with sterile water.…”
Section: Methodsmentioning
confidence: 99%
“…AMF colonization can induce changes in host root exudates ( Ma et al., 2022 ), Zhang’s research found that AMF colonization can affect the level of phenolic acids in cotton root exudates, thereby reducing the incidence rate of Cotton Fusarium Wilt ( Zhang et al., 2012 ). After AMF colonization, it can limit the movement of nematodes and alleviate the invasion of nematodes to tomatoes by affecting the release of root exudates ( Yizhu et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, maize, wheat, and soybean plants produced more organic acids under saline conditions. In addition, AMF supported enhanced betaine biosynthesis, demonstrating that AMF indirectly functions in plant osmoregulation when plants are stressed by salinity [MA et al 2022].…”
Section: D) Amf Mitigates the Saline Conditionsmentioning
confidence: 90%
“…We also found that AMF symbiosis had positive effects on N concentration and aboveground P concentration of cherry tomato, but had negative effects on belowground P concentration, and it is worth noting that these effects varied with AMF species (Figures 3, 5). Although some studies suggested that AMF colonization is beneficial to the uptake of N and P by host plants (Gojon, 2022;Ma et al, 2022), AMF may also cause damage to host plant growth and development by reducing P uptake (Smith et al, 2004). The benefits of AMF symbiosis on nutrient uptake may be influenced by soil nutrient availability and other factors individually or in combination.…”
Section: Cherry Tomato Adapts To Soil Nutrient Reduction Mycorrhizal ...mentioning
confidence: 99%